PENGARUH SUHU TERHADAP PENJERAPAN EKSTRAK ETANOL PDPM (PUCUK DAUN PUCUK MERAH) OLEH KERTAS SARING - Sela Defi Alib Pradani; Sukemi Sukemi; Harra Ismi Farah; Ade Irfan (PROSIDING SEMINAR KIMIA, 2017)
The use of natural extracts from plants mobilized onto solid media as acid-base and pH indicators is being attention of researchers. The mobilization of the ethanol extract of Syzigium oleana shoot leaves has been done and produces paper indicator that can be changed its colorin different pH. This study was designed to determine the effect of temperature on the adsorption of the ethanol extract of S. oleana shoot leavesonto filter paper. The ethanol extract of S. oleana shoot leaves was obtained by using maceration technique for 24 hours with material liquor ratio (MLR) of 1: 7. The adsorption ofethanol extract of S. oleana shoot leaves onto filter paper was carried out at different temperature, i.e. 27°C, 52°C and 81°C with MLR of 1: 100, filter paper weight of 0.2949 ± 0.0035 gram and solution volumeof 30 mL for 2 hours. The results showed that temperature effect on the adsorption of ethanol extract of S. oleana shoot leaves onto filter paper. The % adsorption of S. oleana shoot leaves onto filter paper increased with an increase in the temperature. Keywords : pucuk daun pucuk merah, Syzigium oleana, temperature, adsorption